Learning Model Development Using Moodle E-Learning Software By Implementing Borg And Gall Method - Yudie, Muhardi; Anwar, Syafri; Rukun, Kasman; -, Jasrial (Prosiding International conference on Information Technology and Business (ICITB), 2017)
This research is based on the vastness of Indonesia territory consisting of islands and uneven distribution of population to state education need to follow the development and technological progress which has changed the paradigm of the concept of learning that is conventional.Currently in the midst of technological advances required variations of methods that provide more opportunities for teachers and students to learn independently by utilizing various sources. Teaching and Learning Process is required by utilizing technological elements and utilizing wider learning resources by not abandoning the conventional pattern of direct guidance from the teacher. LESSON LEARNING AND LEARNING TEACHING to the global world today that has meaning in the learning pattern that contains elements of mixed, combined or combined patterns with other patterns to improve the quality of learning to improve. This concept is often also termed by mixing between e-learning with the conventional so-called blended e-learning. Based on the purpose of this study to produce Learning Device Development model by Using Moodle E-Learning Software in Operating System I Course at STMIK Hang Tuah Pekanbaru which valid, practical, and effective.This research is a research development (Reserch and Development) by using Borg and Gall design. The subject of this research is the second semester student (two) Information System Study Program and Informatics Engineering Study Program STMIK Hang Tuah Pekanbaru.The result of this research is the creation of learning tools that are valid, practical, and effective for the course of Operating System I at STMIK Hang Tuah Pekanbaru which is able to improve students creativity abilities in accordance with validation results from the validators.Â Keywords : Blended Learning, Blended elearning, Elearning, Workplace learning